Peran Komunikasi Kepemimpinan Camat Padang Barat Dalam Menjaga Iklim Organisasi (Studi Deskriptif Kualitatif Mengenai Peran Komunikasi Kepemimpinan di Kantor Camat Padang Barat Kota Padang) - Yolla Fren Siska; Dion Eriend (Journal of Media and Communication | E-ISSN : 3063-9581, 2025)
This research aims to find out the Communication Role of the Leadership of the West Padang Sub-district in Maintaining the Organizational Climate. A positive organizational climate is very important to improve organizational performance. Leadership communication is one of the factors that affects the organizational climate. This study uses qualitative descriptive study research methods by collecting data through interviews with 4 research reporters consisting of Leaders and 3 Employees at the West Padang Sub-district Office and through non-participant observations. The results of the study show that leadership that has open and transparent communication, as well as caring and listening, can increase employee trust and maintain a positive organizational climate. Effective leadership communication can help improve employee trust, motivation, and performance, as well as reduce conflict and stress in the workplace. This research has implications that organizations need to maintain leadership communication skills to improve leadership skilss and mantain a positive organizational climate.